Osteopathy for endometriosis and chronic pelvic pain: a Pilot Study = Osteopathie bei Endometriose und chronischen Unterbauchschmerzen : eine Pilotstudie - Sillem, Martin; Klausmeier, Irena (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Pelvic pain is a common problem in gynaecological practice. It is often unclear whether definite causality exists between reported symptoms and objective clinical findings of the female genital tract, and medical or operative treatments do not always achieve long-term resolution of symptoms. Methods: This pilot study investigated 28 patients (age 20-65, median 36.5 years) from a gynaecology practice whose only clinical finding was painful pelvic floor muscle tightness. Following standardised gynaecological and physiotherapist examination, all patients received osteopathic treatment. Pain had been present for a median of 3 years (range 1 month to 20 years). 14 patients had previously confirmed endometriosis. Treatment success was evaluated on consultation with patients in person or in writing. Results: 22 of the 28 participants completed the treatment according to plan. Overall, 17 reported symptom improvement, while 10 of the 14 patients with endometriosis did. Conclusion: Osteopathy is well received by women with painful pelvic floor muscle tightness and appears to be an effective treatment option.